Implementasi Kearifan Lokal Singgi’ dan Retteng Dalam Sastra Lisan Toraja: Kajian Hermeneutik - Dina Gasong (Jurnal Keguruan dan Ilmu Pendidikan, 2017)
This article describes the manifestation of various forms of local wisdom in retteng and Singgi as oral literature through everyday people Toraja. The research methodology used is descriptive qualitative research . The respondents of this study consists of three cultural Toraja, the competent in the field Singgi' And retteng And five respondents Of Elements Academics. Criterion validity of the data used by researchers include : credibility, transferabilitas, dependabilitas, confirmability. The results of this study indicate that local knowledge Singgi ' and retteng in Toraja oral literature include: ethics, social, responsibility, sincerity, justice, truth. Implementation Singgi’ value, and retteng in everyday life, namely : Listen carefully to the speech of others, Ask permission if it will speak, Mutual cooperation, in rambu tuka' and rambu solo', Working tasks according to its function and role, Declare sympathy in the form of soothing words, doing rights and obligations in each activity, not lying, always telling the truth, always looked orang other than the positive side.